Dispersive ionic space charge relaxation in solid polymer electrolytes: I. Experimental system polyethylene oxide - Wagner, Achim; Kliem, Herbert (Journal of applied physics, 2002)
As a model system for solid polymer electrolytes thin polyethylene oxide (PEO) films (0.6–30 μm) are prepared as Al–PEO–Al and as Al–PEO–Si structures with blocking electrodes. Dielectric measurements (capacitance and loss angle) are carried out in a frequency range of 3 mHz⩽f⩽1 MHz in atmospheres of different relative humidities (0%–75%) and at different temperatures (293–313 K). The nominal permittivity varies from 4 at high frequencies to up to 150000 at low frequencies. We find true volume polarization in the high frequency range and a thermally activated space charge relaxation process in the low frequency range. Its time constant exhibits a remarkable dependence on the sample thickness, the relative humidity, the ion concentration, and the temperature. Due to the absorbed dipolar water molecules the activation energy of this process is decreased, leading to higher mobility of the ions. An increase in ion concentration also leads to a lower activation energy. The ions are able to move through the sample to the electrode interfaces and build up ionic space charge. We assume that at the interfaces oxide layers are formed, and these are almost impermeable to these ions. The space charge relaxation process has a broad frequency spectrum. The imaginary part of the nominal permittivity ε″r(ω)∝ωβ has a slope of β=−0.8 to 0.7 above the main relaxation frequency. In the time domain, after application of a voltage step a Kohlrausch behavior of the relaxation current is found. In the short time range we find a current of j∝t−0.3 and in the long time range we find j∝t−1.1. A comparison of the frequency and the time domain by Fourier transform shows that the space charge relaxation process is time invariant for small applied voltages. Nonlinear properties that appear at higher voltages are investigated in the frequency domain and in the time domain.